Power ultrasound and its applications in food processing - Yildiz, Gulcin; Yıldız, Gökçen (Nova Science Publishers, Inc., 2023)
This book includes seven chapters about power ultrasound and its applications in food processing. Chapter One describes the application of ultrasound technology in refining vegetable oils. Chapter Two provides data related to the effect of ultrasound pre-treatment in drying food. Chapter Three presents the effect of sonication treatment on the quality properties of apple-carrot juice. Chapter Four summarizes the ultrasound-assisted extraction of pectin from tropical fruit by-products. Chapter Five discusses the value-added ultrasound technology assuring the safety of seafood. Chapter Six details the comparison of antioxidants and ultrasound treatment on the color, enzymatic browning and bioactive compounds of fresh-cut radishes. Chapter Seven highlights the comparative analysis of ultrasonic probe and water bath systems on the functional properties of whey protein isolate. © 2023 by Nova Science Publishers, Inc. All rights reserved.